Recurrent Nodular Cystic Goiter. In Regards with a Case - José Alberto Puerto Lorenzo; Lidia Torres Aja; Eslinda Cabanes Rojas (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Cystic thyroid nodules in the vast majority of cases are benign, especially if they are pure cysts. Children do not need suppressive treatment with levothyroxine. Puncture may be performed to large cysts to extract its contents. Their reproduction is very frequent, which may involve repeated punctures and the danger of infection. Large cysts reproduce easily, and surgery is necessary, since they rarely respond to medical treatment. We present the case of a 78 year-old male patient, with a history of being an inveterate smoker and hypertensive with treatment, who reported having presented a few months increase in neck volume accompanied by dysphonia and dysphagia to solid foods. Physical examination showed a 5 to 6 cm in diameter tumor in the right antero-lateral region of the neck and part of the left region. It was movable with swallowing and of soft in consistency, without palpable adenopathies. A fine needle aspiration biopsy was performed 3 times, with recurrence and a right lobectomy was performed. The anatomic-pathological study reported nodular goiter with cystic degeneration. In spite of its frequency, communication with teaching purposes is considered important.